A capacitação de gestão estratégica como um instrumento na avaliação do crédito de curto prazo - Caetano, Adalberto Aníbal Monteiro (2001)
This essay enhances the usual Commercial Bank Credit Analysis Model with some strategic points of fundamental importance for shot-term credit operation analysis and approval processes. To reach this goal, not only was engineered a Rating Model pondering cadastral, economic-financial and guarantees analysis, but also includes a company wide integrated vision. Th€! client company strategy is the model foundation and' the focus is on its competitiveness analysis and internai and externai environment. The model final numeric result, within some risk parameters defined by the credit institution, will determine the operation to be approved or denied in compliance with the norms of the Financiai System.